ANALYSIS OF MARKETING STRATEGY CREDIT PROFESSIONALS (Case Study PT RB Danagung Ramulti Yogyakarta) - Purwadhi, Purwadhi; Lantum, MS, Drs. Alex Kahu (Management, 2010)
Abstraction Company in its efforts to achieve the objectives need to pay attention to 2 (two) business environmental factors, namely external and internal factors. External factors are factors that can not be controlled by the company, covering economic, political, legal, technological, demographic and socio-cultural. Internal factors are factors that can be controlled by the company covers all management functions consisting of marketing, finance, personnel, human resources, research and development and enterprise management information system Target market strategy that has been conducted by PT BPR Danagung Ramulti Yogyakarta on professional credit products are prospective customers who have fixed incomes who are in the DIY. Keywords : marketing strategy credit